Mapping Thematic Trends and Analysing Hotspots Concerning the Use of Stem Cells for Cartilage Regeneration: A Bibliometric Analysis From 2010 to 2020 - Xia, Demeng; Wu, Jianghong; Zhou, Feng; Wang, Sheng; Zhang, Zhentao; Zhou, Panyu; Xu, Shuogui (Frontiers in Pharmacology, 2022)
Background: Defects of articular cartilage are a common condition that usually progresses to osteoarthritis with pain and dysfunction of the joint. Current treatment strategies have had limited success in these patients. Stem cells are emerging as a promising option for cartilage regeneration. We aim to summarize the developmental history of stem cells for cartilage regeneration and to analyse the trends and hotspots. Methods: We screened all relevant literature on stem cells for cartilage regeneration from Web of Science during 2010-2020 and analysed the research trends in this field by VOSviewer and CiteSpace. We also summarized previous clinical trials. Results: We screened 1,011 publications. China contributed the largest number of publications (317, 31.36%) and citations (81,376, 48.61%). The United States has the highest H-index (39). Shanghai Jiao Tong University had the largest number of publications (34) among all full-time institutions. The Journal of Biomaterials and Stem Cell Research & Therapy published the largest number of studies on stem cells for cartilage regeneration (35). SEKIYA I and YANG F published the majority of articles in this field (14), while TOH WS was cited most frequently (740). Regarding clinical research on stem cells for cartilage regeneration, the keyword “double-blind” emerged in recent years, with an average year of 2018.75. In tissue engineering, the keyword “3D printing” appeared latest, with an average year of 2019.625. In biological studies, the key word “extracellular vesicles” appeared latest, with an average year of 2018.9091. The current research trend indicates that basic research is gradually transforming into tissue engineering. Clinical trials have confirmed the safety and feasibility of stem cells for cartilage regeneration. Conclusions: Multiple scientific methods were employed to reveal productivity, collaborations, and research hotspots related to the use of stem cells for cartilage regeneration. 3D printing, extracellular vesicles, and double-blind clinical trials are research hotspots and are likely to be promising in the near future. Further studies are needed for to improve our understanding of this field, and clinical trials with larger sample sizes and longer follow-up periods are needed for clinical transformation.